The Relationship Between Motivation and the Level of Patient Adherence to Hypertension Diet at RS Bhakti Asih Brebes - Nuriman, Dedi; Distinarista, Hernandia; Rahayu, Tutik; Hendrawan, Gagah Satria (jurnal cakra medika, 2025)
Background: Hypertension diet is one way to treat hypertension non-pharmacologically, but patient motivation is one factor that can affect a person's adherence to treatment such as a hypertension diet. This study aims to determine the relationship between motivation and the level of patient adherence to a hypertension diet at RS Bhakti Asih Brebes. Method: This quantitative study used a correlational analysis method with a cross-sectional approach. The collected sample was 82 hypertensive patients using a purposive sampling technique. Motivation and dietary adherence were measured using valid and reliable questionnaires. The analysis was carried out using the Chi Square test to determine the relationship between motivation and adherence to a hypertension diet. Results: A total of 49 patients (49%) had high motivation and 59 patients (72%) had high adherence. There was a significant relationship between motivation and adherence to a hypertension diet with a p-value of 0.017. Conclusion: There is a relationship between motivation and adherence to a hypertension diet in hypertensive patients at RS Bhakti Asih Brebes. The hospital can provide health education related to proper hypertension diets through various media, so that patients and families have adequate knowledge about proper hypertension diets and increase patient motivation. Key Words:  Adherence, Diet, Hypertension, Motivation